If n is a non-negative integer, find the n th derivative of x ln x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Let y = x ln x . From the first few derivatives of y we can deduce that: d x n d n y = x n + 1 ( − 1 ) n n ! ( ln x − k = 1 ∑ n k 1 ) . Let us prove that it is true for all n ≥ 1 by induction.
For n = 1, d x d y = x 2 1 − x 2 ln = x 1 + 1 ( − 1 ) 1 1 ! ( ln x − 1 1 ) . Therefore, it is true for n = 1 .
Assume it is true for n , then:
d x n + 1 d n + 1 y = d x d ( d x n d n y ) = d x d ( x n + 1 ( − 1 ) n n ! ( ln x − k = 1 ∑ n k 1 ) ) = x n + 2 ( − 1 ) n n ! ( − 1 ) ( n + 1 ) ( ln x − k = 1 ∑ n k 1 ) + x n + 2 ( − 1 ) n n ! = x n + 2 ( − 1 ) n + 1 ( n + 1 ) ! ( ln x − k = 1 ∑ n k 1 − n + 1 1 ) = x ( n + 1 ) + 1 ( − 1 ) n + 1 ( n + 1 ) ! ( ln x − k = 1 ∑ n + 1 k 1 )
So, it is also true for n + 1 , therefore it is true for all n ≥ 1 .